1998
DOI: 10.1136/adc.78.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin A and beta -carotene concentrations and renal scarring in urinary tract infections

Abstract: Objective-To evaluate the role of vitamin A on renal scarring in recurrent urinary tract infections (UTIs). Design-Twenty three children with UTIs and renal scarring (mean (SD) age 7.3 (3.9) years) and 91 children without renal scarring (6.4 (3.4) years) were studied. All the children had serum vitamin A and -carotene measurements and nutritional evaluation. Renal scarring was assessed by technetium-99m dimercaptosuccinic acid ( The role of vitamin A in recurrent urinary tract infections (UTIs) and urolithiasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 6 publications
3
15
0
Order By: Relevance
“…Serum lutein and zeaxanthin were somewhat lower than those observed in American children by Neuhouser et al [28]. Serum pro-vitamin-A carotenoid concentrations in our healthy children were in a similar range to those of healthy, 12-to 17-year-old American children [28] but higher than those of Filippino [29] or Turkish children [30]. Lycopene serum levels in the healthy Hungarians were as low as those observed in young babies in Honduras [31] in spite of the sufficient lycopene intakes.…”
Section: Discussionmentioning
confidence: 53%
“…Serum lutein and zeaxanthin were somewhat lower than those observed in American children by Neuhouser et al [28]. Serum pro-vitamin-A carotenoid concentrations in our healthy children were in a similar range to those of healthy, 12-to 17-year-old American children [28] but higher than those of Filippino [29] or Turkish children [30]. Lycopene serum levels in the healthy Hungarians were as low as those observed in young babies in Honduras [31] in spite of the sufficient lycopene intakes.…”
Section: Discussionmentioning
confidence: 53%
“…The majority of these studies used laboratory animal models [3,9,14,18,20], and to our knowledge, only two studies of this kind were performed on children [13,21]. There are other studies in which the effects of pentoxifylline, melatonin, and ebselen on prevention of renal scar were examined, but again all were carried out on animal models [10,11,26].…”
Section: Discussionmentioning
confidence: 95%
“…In a study performed on children with recurrent UTI, the severity of renal scarring was revealed to have an inverse correlation with the serum vitamin A concentration [13,15]. There are several factors affecting the degree of renal tissue damage such as bacterial colonization, endotoxin production, interleukin, and oxidative effect [3,13,21]. Vitamin A is needed by all epithelial cells of body tissues.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations